2020
DOI: 10.36222/ejt.646693
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of High Density Polyethylene Addition to Low Density Polyethylene Polymer on Mechanical, Impact and Physical Properties

Abstract: Polyethylene materials are the most widely used polymers which we encountered everywhere in our daily life. Some of the advantages of the polyethylenes are the diversity of production types, corrosion resistance, electrical insulation and recyclability. The main production methods are compression molding, transfer molding, rotational molding, injection molding, gas-assisted injection molding, extrusion and blown film extrusion techniques. It is possible to increase the mechanical properties of low density poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…Table 3 shows that the EB of the biodegradable plastic films varies from 9.04% (run 9) to 168.7% (run 13), which is in the same range as reported by other researchers who manufactured PVA/starch-based biodegradable plastic films [14,17,18]. The EB values of the films obtained in this work are also comparable to LDPE, HDLPE, mixed LDPE-HDPE [42], and HDPE-based degradable films [43]. While researchers reported lower values of the EB [15,16], many others found higher values of the EB [12,13].…”
Section: -2-1-elongation At Breaksupporting
confidence: 85%
See 2 more Smart Citations
“…Table 3 shows that the EB of the biodegradable plastic films varies from 9.04% (run 9) to 168.7% (run 13), which is in the same range as reported by other researchers who manufactured PVA/starch-based biodegradable plastic films [14,17,18]. The EB values of the films obtained in this work are also comparable to LDPE, HDLPE, mixed LDPE-HDPE [42], and HDPE-based degradable films [43]. While researchers reported lower values of the EB [15,16], many others found higher values of the EB [12,13].…”
Section: -2-1-elongation At Breaksupporting
confidence: 85%
“…This result cannot be compared to the TR of other PVA/starch-based biodegradable plastic film, as such data are not found in the literature. However, the TR of the film obtained in this work is comparable to that of polyurethane-based bioplastics (25.66 -45.09 N/mm) [33], LDPE, and mixed LDPE-HDPE films (45 -57 N/mm) [42]. It is even higher than the TR of poly(butylene adipate-co-terephthalate) blown film plasticized by poly(lactic acid) and adipic acid ester both in machine direction (4.63 -8.67 N/mm) and transverse direction (13.19 -16.16 N/mm) [37].…”
Section: -2-3-tear Resistancesupporting
confidence: 49%
See 1 more Smart Citation
“…It has been observed that after the tensile test the tensile strength values of the samples with increasing deformation rates, increase the tensile strength and modulus of elasticity values in contrast to the elongation at break values decrease in the results of the studies in the literature [2]. In another study, it was observed that the thermal aging process of HDPE material increased its mechanical properties, as well as increased hardness values [3]. Harekrushna et al (2019) mixed HDPE material and polypropylene (PP) material in different ratios by mass in their study.…”
Section: Introductionmentioning
confidence: 94%
“…In addition, the hardness of the samples at these compression ratios was measured. Hardness measurements were carried out on 6 different samples each compression process using the X.F Shore-D hardness tester [3] (Figure 6) according to the ASTM D2240 standard [11]. It has been observed that the plastic deformation is at the same values at 10% and 20% compression rates.…”
Section: Figure 4 Dimensions Of the Compression Samplementioning
confidence: 99%